Making It Happen: Middle Managers' Roles in Innovation Implementation in Health Care. Issue 6 (6th October 2018) - Urquhart, Robin; Kendell, Cynthia; Folkes, Amy; Reiman, Tony; Grunfeld, Eva; Porter, Geoffery A.
Abstract: Background: Middle managers are given scant attention in the implementation literature in health care, where the focus is on senior leaders and frontline clinicians. Aims: To empirically examine the role of middle managers relevant to innovation implementation and how middle managers experience the implementation process. Methods: A qualitative study was conducted using the methods of grounded theory. Data were collected through semistructured interviews with middle managers ( N  =   15) in Nova Scotia and New Brunswick, Canada. Participants were purposively sampled, based on their involvement in implementation initiatives and to obtain variation in manager characteristics. Data were collected and analyzed concurrently, using an inductive constant comparative approach. Data collection and analysis continued until theoretical saturation was reached. Results: Middle managers see themselves as being responsible for making implementation happen in their programs and services. As a result, they carry out five roles related to implementation: planner, coordinator, facilitator, motivator, and evaluator. However, the data also revealed two determinants of middle managers' role in implementation, which they must negotiate to fulfill their specific implementation roles and activities: (1) They perform many other roles and responsibilities within their organizations, both clinical and managerial in nature, and (2) they have limited decision‐making power with respect to implementation and must work within the parameters set by upper levels of the organization. Linking Evidence to Action: Middle managers play an important role in translating adoption decisions into on‐the‐ground implementation. Optimizing their capacity to fulfill this role may be key to improving innovation implementation in healthcare organizations.